Study on the Relationship Between Plasma Nitrite and Nitrate Level and Salt Sensitivity in Human Hypertension: Modulation of Nitric Oxide Synthesis by Salt Intake - Fujiwara, Naoto; Osanai, Tomohiro; Kamada, Takaatsu; Katoh, Takeshi; Takahashi, Koki; Okumura, Ken (Circulation (New York, N.Y.), 2000)
Background —High salt intake suppresses the effect of nitric oxide (NO) in the peripheral resistance vessels in animal models. We tested the hypothesis that the modulation of endogenous NO is related to salt sensitivity in human hypertension. Methods and Results —Inpatients with essential hypertension (n=24) were maintained on a normal-salt diet (12 g/d NaCl) for 3 days, a low-salt diet (2 g), a high-salt diet (20 to 23 g), and a low-salt diet for 7 days. Normotensive subjects (n=16) were maintained on the first 2 salt diets. The hypertensive patients whose average 24-hour blood pressure was increased by >5% by salt loading were assigned to group 1 (n=8) and the others to group 2 (n=16). Nitrate plus nitrite (NO x ) was measured by the Griess method, and asymmetrical dimethylarginine (ADMA) by high-performance liquid chromatography. The plasma NO x level during the normal-salt diet was lower in group 1 than in group 2 and the normotensive group. After salt loading, the plasma NO x level was decreased and reversed after the second salt restriction. Plasma ADMA level was increased after salt loading and decreased after salt restriction. The change in plasma NO x level was correlated inversely with those in blood pressure ( r =−0.59, P =0.0007) and plasma ADMA level ( r =−0.64, P =0.003) after salt loading and restriction. Conclusions —Modulation of NO synthesis by salt intake may be involved in a mechanism for salt sensitivity in human hypertension, presumably via the change in ADMA.